STACKing Up Undefined Behaviors. - Regehr, John (Communications of the ACM, 2016)
An introduction to the research paper titled "A Differential Approach to Undefined Behavior Detection" by Xi Wang, Nickolai Zerdovich, M. Frans Kaashoek, and Armando Solar-Lezama is presented.